Avaliação da terapia fotodinâmica associada ao clareamento óptico no tratamento do melanoma cutâneo - Martinelli, Letícia Palombo (2020)
Melanoma is a major public health problem because, despite its low incidence, it has high rates of morbidity and mortality when diagnosed in more advanced stages. Thus, there is a need to develop therapeutic options. Photodynamic therapy (PDT) is a technique based on the use of a compound called photosensitizer (FS), light at an appropriate wavelength to excite the photosensitizer and the oxygen present in the tumor tissue. The photodynamic reaction to induce cell death occurs mainly by the production of singlet oxygen, a highly reactive and oxidative species. In the case of cutaneous melanoma, due to the high concentration of melanin being one of the main biological absorbers, photodynamic therapy has a poor response due to the great limitation of the penetration of light into the tumor. Optical clearing agents (OCAs) have been used to oppose the attenuation of light in tissues, especially in biological samples for confocal microscopy. Our strategy was to use PDT associated with pretreatment of melanoma with clearing agents to optimize tumor irradiation. The FS used was Photodithazine (PDZ) and the clearing agents PEG400 and 1,2-propanediol were associated in a 19: 1 ratio. Analysis by Raman spectroscopy and histopathological analysis was performed in order to evaluate the modification of photodynamic therapy based on biochemical and morphological changes induced in the tumor. The experimental groups were control, TFD and OCA + TFD. PDT was performed after 2h30min of the administration of the PDZ via intraperitoneal. In the Raman analysis, the main changes occurred in protein, lipid and nucleic acid bonds. Analyzing in depth, the OCAs decreased the attenuation of light for regions between 225 and 325 μm, as well as making the tumor more optically homogeneous at all depths. In addition, the photodynamic response was optimized, since it was more homogeneous, demonstrating a more effective light distribution in the tumor. In macroscopic and histological analyzes, both with one PDT session and with two, the groups with pretreatment with OCA showed greater damage to the tumor and greater effectiveness of therapy.